Combating HIV/AIDS Epidemic in Nigeria: Responses from National Open University of Nigeria (NOUN) - Ambe-Uva, Terhemba Nom (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2007)
Universities have come under serious attack because of their lackluster response to HIV/AIDS. This article examines the response of National Open University of Nigeria (NOUN) and its strategic responses in combating HIV/AIDS epidemic. This is achieved by examining NOUN’s basic structures that position the University to respond to the epidemic; and second, by assessing HIV/AIDS strategies and policy framework the University has put in place. An interpretative epistemological stance was used for this study, and a qualitative research involving focus group discussion (FGD) and analysis of secondary data was carried out. Results showed that NOUN has identified the impact the epidemic has on the university, although it has yet to institutionalize an HIV/AIDS policy. NOUN’s Draft Service Charter, however, has identified the fight against HIV/AIDS as a core mandate of the University, and the introduction of HIV/AIDS certification programs can be viewed as proactive policies in response to the epidemic. Results of this study are discussed in terms of their relevance to future research and the impact such policy frameworks may have on combating the epidemic, both within the University and the wider community.